Interleukin-1–mediated hematopoietic cell regulation in the aorta-gonad-mesonephros region of the mouse embryo - Orelio, Claudia (American Society of Hematology, 2008)
Hematopoiesis during development is a dynamic process, with many factors involved in the emergence and regulation of hematopoietic stem cells (HSCs) and progenitor cells. Whereas previous studies have focused on developmental signaling and transcription factors in embryonic hematopoiesis, the role of well-known adult hematopoietic cytokines in the embryonic hematopoietic system has been largely unexplored. The cytokine interleukin-1 (IL-1), best known for its proinflammatory properties, has radioprotective effects on adult bone marrow HSCs, induces HSC mobilization, and increases HSC proliferation and/or differentiation. Here we examine IL-1 and its possible role in regulating hematopoiesis in the midgestation mouse embryo. We show that IL-1, IL-1 receptors (IL-1Rs), and signaling mediators are expressed in the aorta-gonad-mesonephros (AGM) region during the time when HSCs emerge in this site. IL-1 signaling is functional in the AGM, and the IL-1RI is expressed ventrally in the aortic subregion by some hematopoietic, endothelial, and mesenchymal cells. In vivo analyses of IL-1RI–deficient embryos show an increased myeloid differentiation, concomitant with a slight decrease in AGM HSC activity. Our results suggest that IL-1 is an important homeostatic regulator at the earliest time of HSC development, acting to limit the differentiation of some HSCs along the myeloid lineage.